Kandungan Fraksi Serat Ransum Pellet Unggas Dengan Penggunaan Tepung Indigoferazollingeriana - Putri Jati; Triani Adelina; Dewi Ananda Mucra (Jurnal Peternakan, 2017)
This study aims to evaluation the effect of Indigofera zollingeriana flour utilization inpoultry pellet ration on the content of the fiber fraction ,namely : Neutral Detergent Fiber (NDF), Acid Detergent Fiber (ADF), Acid Detergent Lignin (ADL), hemicelluloses and cellulose. The experimental design used Completely Randomized Design(CRD),which consists of 4 treatments and 5 replicates. The treatments were the level of Indigofera zollingeriana flour utilization that were T0 = 0% Indigofera zollingeriana  (control),T1  =  5%  Indigofera  zollingeriana,  T2  =10%  Indigofera  zollingeriana,  T3  =  15%  Indigofera zollingeriana.  The  results showed that the Indigofera zollingeriana utilization had no significant effect (P>0.05) on the content of NDF, hemicellulose, cellulose but had  significantly effect (P<0.05) to the content of ADF and highly significant effect (P<0.01) on the content of ADL. It was concluded that the use of 15% Indigofera zollingerian alowered the content ADF and ADL, unable to reduce the content fNDF and unable to increase the content of hemicellulose and cellulose.The use of 15% Indigofera zollingeriana is t h e b e s t  30.39% NDF; 9.42% ADF; 2.25% ADL; 20.98% hemicellulose and 4.53% cellulose.